The discrimination against domestic helpers, and social-spatial segregation in the beaches of Lima - Rottenbacher, Jan Marc (2015)
This study analyses the influence of political conservatism on support for discrimination against domestic labourers and positive attitudes toward socio-spatial segregation in the use of Lima’s beaches in a sample of university undergraduate students. Right-wing authoritarianism (RWA) and social dominance orientation (SDO) were assessed. Intolerance to ambiguity was evaluated as a measure of cognitive rigidity. A path analysis proposes that SDO and intolerance of ambiguity exert a direct influence on support for discrimination against domestic labourers. Also, SDO and RWA exert a direct influence on positive attitudes toward socio-spatial segregation in the beaches. Finally, a positive correlation between discriminatory attitudes and a positive attitude toward socio-spatial segregation was observed.